The Effect Of Economic Growth and Government Expenditure On Human Development In Palu City - Andi Heman Jaya (Institute of Computer Science (IOCS), 2021)
The purpose of this study was to determine and analyze the effect of economic growth and government spending simultaneously and partially on human development in Palu CityThis research is classified into the type of explanatory research that examines the causal relationship between two or more phenomena with using secondary data from the publication of documentation from the Central Statistics Agency (BPS) of Palu City, the Financial Bureau of the Palu City Secretariat or the Regional Revenue Agency (Bapenda) for the period 2012-2020. The data analysis technique uses multiple linear regression analysis with the results of the study showing that the variables of economic growth and government spending simultaneously have a positive and significant effect on human development in Palu City, with a Sig-F value of 0.000 < 0.05. The variable of economic growth has a positive and significant effect on human development in Palu City with a Sig-t value of 0.000 < 0.05; and the government expenditure variable has a positive and significant effect on economic growth in Palu City with a Sig-t value of 0.009 < 0.05.